2020
DOI: 10.1021/acs.orglett.0c00798
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Bridged Azacycles and Propellanes via Nitrene/Alkyne Cascades

Abstract: A nitrene/alkyne cascade reaction terminating in C–H bond insertion to form functionalized bridged azacycles from carbonazidates is presented. Due to an initial Huisgen cyclization, all carbonazidates reacted with the alkyne in an exo mode in contrast to the use of sulfamate esters, which react predominately in an endo mode. Substrates with different ring sizes as well as different aryl and heteroaryl groups were also explored. Variation of the nitrene tether showed that 7-membered rings were the maximum ring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 65 publications
(19 reference statements)
1
8
0
Order By: Relevance
“…By tuning the linker in the substrates, diverse bridged, fused, spiro, or even caged products with at least one oxygen atom in the rings can be obtained. Very recently, they (Wang and May, 2020) further developed a rhodium(II)catalyzed nitrene/alkyne cascade reaction for synthesis of bridged heterocycles (Figure 13C). Although the yields are only moderate, the structural diversity is remarkable with least one oxygen atom and one nitrogen atom in the products.…”
Section: Polycyclic Heterocycles With Sp 3 Centersmentioning
confidence: 99%
“…By tuning the linker in the substrates, diverse bridged, fused, spiro, or even caged products with at least one oxygen atom in the rings can be obtained. Very recently, they (Wang and May, 2020) further developed a rhodium(II)catalyzed nitrene/alkyne cascade reaction for synthesis of bridged heterocycles (Figure 13C). Although the yields are only moderate, the structural diversity is remarkable with least one oxygen atom and one nitrogen atom in the products.…”
Section: Polycyclic Heterocycles With Sp 3 Centersmentioning
confidence: 99%
“…Thus, esters have been efficiently used as solvents in various rhodium-catalyzed carbene reactions. 14,15 To the best of our knowledge, the only intermolecular carbene reaction with esters was reported in 2018 by Davies,9 where donor/acceptor carbenes 12 reacted with esters to form tertiary alcohols 16 (Scheme 1c).…”
mentioning
confidence: 99%
“…In a recent paper, we reported a Huisgen cyclization/ carbene cascade reaction to construct bridged azacycles and propellanes. 15 Investigations showed that the best solvent for that transformation was isopropyl acetate (i-PrOAc). However, an unexpected imidate 20 was found as a byproduct in 34% yield (Scheme 2).…”
mentioning
confidence: 99%
See 2 more Smart Citations